Antibiotic prescriptions among dentists across Norway and the impact of COVID-19 pandemic - Farnoush Tousi; Mohammed Al Haroni; Stein Atle Lie; Bodil Lund (BMC, 2023)
Abstract Background The prescription of antibiotics in dental practice contributes significantly to the total use of antibiotics in primary healthcare. This study aimed to evaluate antibiotic prescription in dental practice during the years 2016-2021 in Norway and their relative contribution to national outpatient consumption and to investigate the influence of age, gender, geographic region, and COVID-19. A further aim was to review differences in prescribing patterns to verify effect of governmental strategies to reduce over-prescribing of antibiotics. Methods This register study investigated the national antibiotic prescription between 2016 and 2021. Data was obtained from the Norwegian prescription register, the Norwegian Institute of Public Health and Statistics Norway. The consumption of 12 common antibiotics was measured using WHO defined daily doses (DDDs), DDD per 1000 inhabitants per day (DIDs 1000). Results A total of 6,049,445 antibiotic prescriptions of the 12 investigated compounds were issued in primary care during the study period. Dentists accounted for 942,350 prescriptions corresponding to 15.6% of the total. An overall decrease in the number of prescriptions by health professions other than dentists during the 5 years (IRR = 0.92, 95% CI:0.92-0.93, p < 0.001) was observed. For dentists a slight increase in the number of prescriptions (IRR = 1.01, 95% CI: 1.01-1.01, p < 0.001) was seen over the study period. The increase of antibiotic prescriptions in dentistry was more pronounced during the COVID-19 pandemic. The 4 most prescribed type of antibiotics based on average number of DDDs of the total period 2016-2021 were in descending order; phenoxymethylpenicillin (1,109,150) followed by amoxicillin (126,244), clindamycin (72,565), and metronidazole (64,599). An unexpected finding was that the prescription of the combination compound amoxicillin/clavulanic acid had significantly increased in dentistry during the last 5 years. Geographic, gender, and age differences in the rates of prescriptions were also seen. The data revealed that there are seasonal variations in dental prescriptions. Conclusions Noticeable differences exist in prescribing patterns of antibiotics in the last 5 years. Restricted access to dental care due to COVID-19 may have resulted in increased antibiotic prescribing in dentistry as opposed to an otherwise downward trend. Despite national guidelines there is still a need for improvement of antibiotic stewardship in dentistry and to define effective methods to disseminate information.